Oesophageal rhabdomyoma. Issue 7 (1st July 2000) - Roberts, F; Kirk, A J B; More, I A R; Butler, J; Reid, R P
Abstract : Extracardiac rhabdomyomas are rare benign tumours showing striated muscle differentiation. Seventy percent of these lesions occur in the head and neck region. The most common sites for these lesions are the larynx, pharynx, and the floor of the mouth. There has been only one previous report of a rhabdomyoma of the oesophagus; two further cases are described.